The Role of the Medical Committee in Efforts to Resolve Medical Disputes in Hospitals - Minar Mushari; Redyanto Sidi; Irsyam Risdawati (Fakultas Hukum Dehasen, 2026)
Medical disputes continue to grow in complexity as public expectations for high-quality healthcare and legal awareness increase. Within this context, the Medical Committee holds a crucial role as an internal hospital mechanism responsible for providing professional and objective assessments of medical actions before disputes escalate to external forums. This study aims to examine the normative position, authority, and effectiveness of the Medical Committee in the resolution of medical disputes within the framework of existing legislation. The research employs a normative juridical method by analyzing the provisions of the Health Law No. 17 of 2023, Hospital Law No. 44 of 2009, Medical Practice Law No. 29 of 2004, and Minister of Health Regulation No. 755/MENKES/PER/IV/2011. The findings indicate that the Medical Committee possesses strong legal legitimacy to conduct medical audits, maintain professional standards, and provide technical recommendations in dispute resolution. However, its effectiveness varies due to inconsistent implementation, overlapping authority with other internal bodies, and the absence of uniform operational guidelines. This study highlights the need for strengthened regulation and standardized procedures to enhance the role of the Medical Committee as an effective early-stage dispute filter and a provider of legal certainty within hospital-based medical dispute mechanisms..